2016
DOI: 10.1371/journal.pone.0151674
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypic Characterization of the Human Renal Mononuclear Phagocytes Reveal a Co-Ordinated Response to Injury

Abstract: Mammalian tissues contain networks of mononuclear phagocytes (MPh) that sense injury and orchestrate the response to it. In mice, this is affected by distinct populations of dendritic cells (DC), monocytes and macrophages and recent studies suggest the same is true for human skin and intestine but little is known about the kidney. Here we describe the analysis of MPh populations in five human kidneys and show they are highly heterogeneous and contain discrete populations of DC, monocytes and macrophages. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Of note, human CD16 + monocytes are now conventionally subdivided on the basis of CD14 expression into intermediate and nonclassical subsets ( 63 ) and have been shown to circulate in higher numbers in CKD, atherosclerosis and multiple other pro-inflammatory conditions ( 64 , 65 ). Despite the demonstrated expansion of these populations in CKD and their association with CKD progression ( 64 ), the extent to which they infiltrate the renal parenchyma and contribute to renal inflammation and fibrosis during CKD is incompletely understood ( 66 ). Further investigation of the role of CX3CL1 in mediating inflammatory monocyte subset activities in human CKD will be of value in elucidating these issues.…”
Section: The Role Of the Cx3cl1-cx3cr1 Axis In Chronic Kidney Disease: Evidence From Studies Of Human Tissue And Cellsmentioning
confidence: 99%
“…Of note, human CD16 + monocytes are now conventionally subdivided on the basis of CD14 expression into intermediate and nonclassical subsets ( 63 ) and have been shown to circulate in higher numbers in CKD, atherosclerosis and multiple other pro-inflammatory conditions ( 64 , 65 ). Despite the demonstrated expansion of these populations in CKD and their association with CKD progression ( 64 ), the extent to which they infiltrate the renal parenchyma and contribute to renal inflammation and fibrosis during CKD is incompletely understood ( 66 ). Further investigation of the role of CX3CL1 in mediating inflammatory monocyte subset activities in human CKD will be of value in elucidating these issues.…”
Section: The Role Of the Cx3cl1-cx3cr1 Axis In Chronic Kidney Disease: Evidence From Studies Of Human Tissue And Cellsmentioning
confidence: 99%
“…81 85 In the human kidney, cDC1, cDC2, and pDC were identified. 86 Although the presence of the DC signature in tumors correlates with sensitivity to CBT in patients with kidney cancer, 87 the RCC TME can skew renal myeloid DC and pDC toward an immature state rendering them incapable of migrating to the draining lymph node 88 (figure 2). In culture, RCC cells release vascular endothelial growth factor (VEGF) and IL-6, which can inhibit the ability of DC to stimulate T cells.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…Our hypothesis is that sDQB2 originates from the graft, considering the association between poor graft function and high HLA-DQB2 expression in PIB, observed in our previous study (Mine et al, 2018), as well as in 1-year posttransplant biopsies, observed in our previous analysis (Mine et al, 2018) using a publicly available microarray dataset (GSE22459) (Park et al, 2010). As for the cell source of sDQB2 within the graft, we speculate that they could be graft infiltrating CD1c + DCs, which are very efficient antigen-presenting cells (Kurts et al, 2020), normally present in the kidney (Kurts et al, 2020;Leone et al, 2016;Loverre et al, 2007;Woltman et al, 2007;Zuidwijk et al, 2012) and with an increased number in biopsies with rejection (Kurts et al, 2020;Loverre et al, 2007;Zuidwijk et al, 2012). Interestingly, Lim et al (2020) recently…”
Section: Discussionmentioning
confidence: 67%